A Combinatorial Assessment Methodology for Complex Policy Analysis - Francesca Medda; Peter Nijkamp (Tinbergen Institute, 1999)
This paper proposes an integrated evaluation methodology which serves to alleviate the limitations of a singleevaluation approach by combining different assessment and policy analysis methods. It is demonstrated that, in a multi-criteria context, a so-called combinatorial framework can cope with the serious limitations of the above mentionedapproach, in particular the potential redundancy in the information table and the subjectivity of the 'expert' in theweight choice procedure. We use rough set analysis as a tool for classifying and identifying the most critical decisionattributes, while next a multi-criteria analysis is deployed in combination with other methods. We apply this newcombinatorial assessment methodology to an illustrative case study on transportation planning, where the coreassessment methodology is formed by a combined qualitative-quantitative regime analysis, extended withcomplementary approaches. The results of the analysis indicate that the combinatorial method indeed has theflexibility and capacity to assess complex multidimensional policy issues.
Keywords: 330; Entscheidung; Bewertung; Theorie